Peningkatan Keterampilan Menulis Puisi Melalui Teknik Akrostik pada Peserta Didik Kelas VIII.11 UPT SPF SMP Negeri 3 Makassar - Barhun, Mohamad Syahrul; Azis, Azis; Sultan, Sultan (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to improve the poetry writing skills of students in class VIII.11 UPT SPF SMP Negeri 3 Makassar through acrostic techniques. This research uses a type of action research. The implementation of the action was carried out for two cycles, each ermine the improvement of students' writing skills, researchers used observation sheets and poetry writing tests for each cycle. consisting of two meetings. Each cycle went through the stages of planning, implementation, observation, and evaluation. To determine the improvement of students' writing skills, researchers used observation sheets and poetry writing tests for eactotalingThe subjects in this study were students of class VIII.11 UPT SPF SMP Negerir in the academic year 2023/2024, totalling 34 students. The data analysis technique used was qualitative data analysis technique. Based on the results of the study, during the implementation of cycles I and II, the average score of students was 63.2 for cycle I and 78.8 foII,cycle II. In cycle I, there were 17 students who reached the criteria for achieving learning objectives (KKTP), while in cycle II there were 28 students who reached KKTP. The results showed that the application of the acrostic technique in the poetry learning process was able to improve poetry writing skills in students of class VIII.11 UPT SPF SMP Negeri 3 Makassar.